Viralité et analyse du discours : un exemple atypique, #MeToo - Sandrine Reboul-Touré (MediAzioni)
We present an analysis exploring the notion of virality in the field of discourse analysis, whereas the notion is usually used in the field of information and communication sciences. The present research develops a discourse analysis based on keywords, here, #MeToo, which has a special status since it is also used outside the internet. The diversity of linguistic points of view such as borrowing, spelling, neologism, neological matrix, averbal phrase, digital statement make #MeToo an atypical and complex hashtag. Its propagation (2017-2022) through numerous discourses to placards in feminist demonstrations and even on hands and faces transforms the hashtag, which acquires another status: naming a social movement. This example shows that virality can enrich three notions: the event, the “formula” and the circulation of discourses.